A novel approach for rectal trauma. The use of a transanal platform to repair a combined high-velocity rectal gun fire wound - Guraieb-Trueba,Montserrat (2020)
Abstract Up to 80 % of the rectal injuries reported in US trauma centers occur secondary to firearm injuries. Rectal gunshot wounds are associated with significant morbidity and mortality. Diverse surgical approaches and techniques have been described; however, controversy persists regarding the best management for these complex injuries. Nowadays, no single approach has proven to provide optimal results when dealing with these injuries. We present a case of a young male that suffered a combined (intra-extraperitoneal) gun shot gun to the rectus and the use of a transanal platform to repair it.